Analysis of the Word Laun in the Quran: A Semantic Meaning Study Using the Visible Spectrum Theory Approach: Analisis kata Laun dalam al-Quran: Kajian Semantika Makna dengan pendekatan Teori Spektrum kasatmata - Mohammad Irfan Farraz Haecal; Zumrotun Khasanah; Wildan Taufik (Tunas Harapan Ummat Foundation, 2024)
This study aims to understand the meaning of the word launun in the Quran, which is mentioned nine times, using Isaac Newton’s theory of the visible spectrum. This research employs a qualitative method with a literature study approach, meaning it does not take direct samples but is based on existing writings and general views. The main question of this research is to understand the spectrum of light in the Quran and its semantics. The study concludes that the color spectrum in the Quran consists of six color ranges: Red, White, Yellow, Green, Blue, and Black. Based on semantic studies, this indicates that colors in the Quran reflect a clear boundary between each other. This aligns with Isaac Newton’s theory of the visible spectrum, which states that there is a boundary between each color until they are mixed. Further research is needed to explain the color spectrum in more detail and semantic studies to explore the meanings within the verses of the Quran